Notes on the St. Theodore’s church iconostasis from Iași. Technique of execution, stylistically description and state of conservation - Bogdan Ungurean (Anastasis: Research in Medieval Culture and Art, 2018)
This paper proposes an overview of the iconostasis of the Church St. Theodore’s of Iaşi with mention of the execution technique, stylistic description of the registers that compose the iconostasis and also description of the state of conservation of the assembly. Information about the iconostasis is preceded by a brief description of the building architecture. The material is part of a research project that dealt with the technical expertise of the monument and its artistic components.